Numerical simulations of two-phase flow in proton exchange membrane fuel cells using the volume of fluid method - A review - Rui B. Ferreira (2015)
Water management in proton exchange membrane (PEM) fuel cells, i.e., balance between membrane drying and liquid water flooding, is a major aspect in the operation of these devices. Flooding results in gas liquid two-phase flow that causes high pressure drops, flow maldistribution and poor cell performances. Limitations related to the experimental techniques dedicated to investigate the dynamics of liquid water in a PEM fuel cell have motivated researchers to conduct computational modeling and simulation to better understand the two-phase flow and its implications. Among different mathematical models employed, the volume of fluid (VOF) method is the most popular approach. This paper reviews the VOF numerical simulations of two-phase flow in PEM fuel cells. The focus of the study, numerical details, and main outcomes of each research work are discussed during this review. Moreover, recommendations for future simulations as well as challenges of applying the VOF method to PEM fuel cells are presented.